The Effects of Organizational Socialization Tactics on Newcomer Job Satisfaction and Engagement: Does Core Self-Evaluation Important? - Satria Maulana Putra,; Mahdani Ibrahim,; Amri, (Technium Social Sciences Journal, 2020)
One hundred and fifty-nine new workers in the government sector in Aceh Besar District were sampled to investigate whether their job satisfaction and engagement was influenced by organizational socialization tactics. Core self-evaluation is considered an important factor for newcomers who interact between organizational socialization tactics towards the outputs who were investigated in this study. Primary research data obtained from the results of questionnaires distributed to respondents who previously we have set. Structural Equation Modeling (SEM) supported by the AMOS 24 program is used to produce an accurate analysis of the primary data of this study. Based on the results of the analyzed data it was found that job satisfaction and work engagement of newcomers within the government sector organization in Aceh Besar District were influenced by factors of organizational socialization tactics in the organization itself. In addition, the results of the investigation data analysis also found that the core self-evaluation factor is important to be taken into account by newcomers when entering the organization that is now observed. Whether the results of this investigation in other places experienced the same thing, also discussed.